Network Pharmacology Analysis of the Therapeutic Potential of Colchicine in Acute Lung Injury - Fei Sun; Lijuan Zhang; Lulu Shen; Chunman Wang (International Journal of Clinical Practice)
Background. This study employed integrated network pharmacology approach to explore the mechanisms underlying the protective effect of colchicine against acute lung injury (ALI). Methods. We analyzed the expression profiles from 13 patients with sepsis-related ALI and 21 controls to identify differentially expressed genes and key modules. ALI-related genes were curated using databases such as DisGeNET, Therapeutic Target, and Comparative Toxicogenomics Database to curate ALI-related genes. Drug target fishing for colchicine was conducted using the DrugBank, BATMAN-TCM, STITCH, and SwissTargetPrediction. Potential drug-disease interactions were determined by intersecting ALI-associated genes with colchicine target genes. We performed comprehensive pathway and process enrichment analyses on these genes. A protein-protein interaction network was constructed, and topological analysis was executed. Additionally, an ALI mouse model was established to evaluate the effect of colchicine on CXCL12 and CXCR4 levels through western blot analysis. Results. Analysis revealed 23 potential colchicine-ALI interaction genes from the intersection of 253 ALI-associated genes and 389 colchicine targets. Functional enrichment analysis highlighted several inflammation-related pathways, such as cytokine-mediated signaling pathway, CXCR chemokine receptor binding, NF-kappa B signaling pathway, TNF signaling pathway, and IL-17 signaling pathway. The protein-protein interaction network demonstrated complex interactions for CXCL12 and CXCR4 among other candidate genes, with significant topological interaction degrees. In vivo studies showed that colchicine significantly reduced elevated CXCL12 and CXCR4 levels in ALI mice. Conclusion. Our findings suggest that colchicine’s therapeutic effect on ALI might derive from its anti-inflammatory properties. Further research is needed to explore the specific mechanisms of colchicine’s interaction with sepsis-induced ALI.